2003
DOI: 10.1124/jpet.103.052852
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Product Ligand of the Oxysterol Receptor, Liver X Receptor

Abstract: Natural products have been identified as ligands for a number of members of the nuclear hormone receptor (NHR) superfamily. Often these natural products are used as dietary supplements to treat myriad ailments ranging from perimenopausal hot flashes to hypercholesterolemia and reduced cognitive function. Examples of some natural product ligands for NHRs include genestein (estrogen receptors NR3A1 and NR3A2), guggulsterone (farnesoid X receptor NR1H4), and St. John's wort (pregnane X receptor, NR1I2). In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Krasowski, unpublished data). We also found that paxilline, a fungal metabolite reported to activate LXRα and LXRβ [30], also activated zebrafish, Xenopus laevis, and Xenopus tropicalis LXRs, although with much lower efficacy than T-0901317 (Tables 1 and 2). …”
Section: Ligand Specificity Of Vertebrate Lxrsmentioning
confidence: 74%
“…Krasowski, unpublished data). We also found that paxilline, a fungal metabolite reported to activate LXRα and LXRβ [30], also activated zebrafish, Xenopus laevis, and Xenopus tropicalis LXRs, although with much lower efficacy than T-0901317 (Tables 1 and 2). …”
Section: Ligand Specificity Of Vertebrate Lxrsmentioning
confidence: 74%
“…Distinct pathogen-specific molecules acting as pathogen-associated molecular patterns and/or as LXR ligands likely cause the divergent outcomes of LXR activation in these infection models. A report that the fungal metabolite paxilline is a potent LXR agonist supports this proposition (50). In addition, M. tuberculosis contains an array of unique lipid components in its outer cell envelope that could act as potential LXR ligands.…”
Section: Discussionmentioning
confidence: 94%
“…Radioligand binding assays were performed using either the charcoal separation or scintillation proximity technology as described previously (Palmer et al, 2000;Bramlett et al, 2003). Tritiated radioligands were used for all assays with the exception of thyroid hormone receptor (TR) and included dexamethasone (GR), methyltrienolone (R1881) (AR), aldosterone (MR), promegestone (R5020) (PR), GW4064 (FXR), T1317 (liver X receptor ␣, LXR␣), 9-cis retinoic acid, 17␤-estradiol (ER), peroxisome proliferator-activated receptor (PPAR) ␣ and PPAR␦ (LY427697), and PPAR␥ (LY509547) (Brooks et al, 2001;Xu et al, 2004).…”
Section: Methodsmentioning
confidence: 99%